IMPACT OF SERVICE QUALITY, CUSTOMER COMPLAINT HANDLING AND BANKING INNOVATION ON LOYALTY WITH THE MEDIATING ROLE OF CUSTOMER SATISFACTION - Shakeel Aziz; Dr. Imran Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
In the current competitive environment, banks considered customer satisfaction as a big challenge. Globally every firms try to satisfy its customer through quality services, which is essential to retain its customers. The purpose of the research is to study the factors’ impact like “Quality Service, Complaint Handling & Banking Innovation” on Customer Loyalty taking Customer Satisfaction as a mediator in the Pakistani banking context like MCB. In this study the conventional banking sector of Pakistan like MCBhas been taken. It is a quantitative based research. The population of the study was the walk-in customer of the bank. It was a survey base research in which “questionnaires” have been used, based on 5 point Likert scale. The data collection instrument has been checked before testing the hypothesis. Simple linear regression, SEM model and SPSS used for the data analysis. The result of the research has concluded as follows: There is a positive and significant influence exists between Service Quality and Customer Loyalty. The relationship between Complaint Handling and Customer Loyalty is positive and significant. Banking Innovation and Customer Loyalty showed a positive and significant relationship. Customer Satisfaction has a positive and significant effect directly on Customer Loyalty. Service Quality has a positive, significant and direct impact on the level of Customer Satisfaction. Complaint Handling has positive, significant and direct effects on Customer Satisfaction. Banking Innovation has a positive, significant and direct impact on Customer Satisfaction. Service Quality has an indirect effect but with a positive and significance influence on Customer Loyalty via Customer Satisfaction.